Modeling Congenital Disorders of N-Linked Glycoprotein Glycosylation in Drosophila melanogaster - Frappaolo, Anna; Sechi, Stefano; Kumagai, Tadahiro; Karimpour-Ghahnavieh, Angela; Tiemeyer, Michael; Giansanti, Maria Grazia (Frontiers in Genetics, 2018)
Protein glycosylation, the enzymatic addition of N-linked or O-linked glycans to proteins, serves crucial functions in animal cells and requires the action of glycosyltransferases, glycosidases and nucleotide-sugar transporters, localized in the endoplasmic reticulum and Golgi apparatus. Congenital Disorders of Glycosylation (CDGs) comprise a family of multisystemic diseases caused by mutations in genes encoding proteins involved in glycosylation pathways. CDGs are classified into two large groups. Type I CDGs affect the synthesis of the dolichol-linked Glc3Man9GlcNac2 precursor of N-linked glycosylation or its transfer to acceptor proteins. Type II CDG (CDG-II) diseases impair either the trimming of the N-linked oligosaccharide, the addition of terminal glycans or the biosynthesis of O-linked oligosaccharides, which occur in the Golgi apparatus. So far, over 100 distinct forms of CDGs are known, with the majority of them characterized by neurological defects including mental retardation, seizures and hypotonia. Yet, it is unclear how defective glycosylation causes the pathology of CDGs. This issue can be only addressed by developing animal models of specific CDGs. Drosophila melanogaster is emerging as a highly suitable organism for analyzing glycan-dependent functions in the central nervous system (CNS) and the involvement of N-glycosylation in neuropathologies. In this review we illustrate recent work that highlights the genetic and neurobiologic advantages offered by Drosophila melanogaster for dissecting glycosylation pathways and modeling CDG pathophysiology.